Exploring the Perspectives of Tribhuvan University Undergraduate Students Toward Business Statistics: A Study of Shanker Dev Campus - Khadka, Srijana (Nepal Journal of Multidisciplinary Research, 2023)
This comprehensive study explored the intricate determinants of Tribhuvan University undergraduate students' attitudes toward business statistics, employing a mixed-methods approach to capture the multifaceted nature of their perceptions. Grounded in theoretical frameworks such as the Theory of Reasoned Action, Expectancy-Value Theory, Cognitive Load Theory, and Effort-Performance Theory, the research analyses the relationship and influence of cognitive competence, value, difficulty, and effort with students' attitudes. With a large sample size of 328 students, the study employs a descriptive and causal-comparative research design to uncover significant correlations between these variables. The regression results highlight the predictive power of cognitive competence, value, difficulty, and effort on students' attitudes, providing valuable insights for educators and stakeholders in enhancing the learning experience in business statistics. The findings underscore the dynamic interplay of these factors over time, emphasizing the need for tailored educational strategies and interventions to foster positive attitudes and outcomes in the field.